Introducing bromine to the molecular structure as a strategy for drug design (Journal of Medical Science, 2024)
Nowadays, the search for new pharmaceuticals has resulted in the development of thousands of new substances. One of the effective drug design strategies is to modify a previously obtained and studied substance. A very popular modification is the introduction of halogens into the structure of drugs, most often of which being fluorine or chlorine atoms. However, the introduction of bromine into the structure of a potential drug also has a number of advantages. A good example would be natural substances extracted from marine organisms, which have been studied and proven to be effective against various diseases, including antibiotic therapy of resistant bacteria. Numerous studies justify the usage of bromine and its isotopes in therapy (both in diagnostic imaging and radiotherapy). To better explain the impact of “bromination,” numerous researchers have described such a phenomenon as “halogen bond.” Due to the presence of the so-called “sigma-hole” in the halogen atom of an organic molecule, it is possible to form these bonds, which results in a change in intermolecular and intramolecular interactions. Such changes can favorably affect drug-target interactions. The advantages of “bromination” include an increase in therapeutic activity, a beneficial effect on the metabolism of the drug, and an increase in its duration of action. Besides, the phenomenon of the heavy atom effect can be used to increase the effectiveness of photodynamic therapy and radiosensitization. Unfortunately, “bromination” is not without it’s drawbacks, which may include increased toxic effects and accumulation in the organism.